2006
DOI: 10.1002/pmic.200500321
|View full text |Cite
|
Sign up to set email alerts
|

Profilin 1 obtained by proteomic analysis in all-trans retinoic acid-treated hepatocarcinoma cell lines is involved in inhibition of cell proliferation and migration

Abstract: Previous studies have shown that all-trans retinoic acid (ATRA) suppresses growth of hepatocarcinoma cell in vitro. To understand the underlying mechanisms, we investigated the protein expression profiles by 2-DE in hepatocarcinoma cell line SMMC-7721 treated with ATRA. Our results reveal that six proteins were differently expressed in response to ATRA. Using MS and database searching, they were identified as profilin 1, phosphoglycerate kinase 1, RuvB-like 1, alpha-enolase, pyridoxal kinase and F-actin cappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 40 publications
3
59
1
Order By: Relevance
“…Our previous studies showed that silencing profilin1 expression leads to faster motility of both normal human mammary epithelial cells (HMEC) and metastatic MDA-MB-231 (MDA-231) breast cancer cell line; conversely, even a moderate overexpression of profilin1 dramatically suppresses motility of MDA-231 and BT474 breast cancer cell lines (11)(12)(13). This paradoxical effect of profilin1 in cell migration has also been reported for hepatocarcinoma cells where profilin1 expression also appears down-regulated (14). These findings suggest that profilin1's role in cell migration is complex and contextual.…”
mentioning
confidence: 92%
“…Our previous studies showed that silencing profilin1 expression leads to faster motility of both normal human mammary epithelial cells (HMEC) and metastatic MDA-MB-231 (MDA-231) breast cancer cell line; conversely, even a moderate overexpression of profilin1 dramatically suppresses motility of MDA-231 and BT474 breast cancer cell lines (11)(12)(13). This paradoxical effect of profilin1 in cell migration has also been reported for hepatocarcinoma cells where profilin1 expression also appears down-regulated (14). These findings suggest that profilin1's role in cell migration is complex and contextual.…”
mentioning
confidence: 92%
“…After 24 h, a transwell assay was used to monitor in vitro cell migration as previously described [12]. Briefly, 1×10 4 tumor cells in 0.5% BSA-DMEM were placed in the upper chamber of the transwell unit and 0.5% BSA-DMEM containing 0.5% FBS was placed in the lower chamber.…”
Section: Transwell Migration Assaymentioning
confidence: 99%
“…Lysates were clarified by centrifugation at 15000×g for 10 min at 4°C. The protein concentration was determined using a modified Lowry assay [11,12]. Proteins (60 μg) were run on a 10% SDS polyacrylamide gel and electrophoretically transferred onto a nitrocellulose membrane.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Experimental manipulations restoring the normal expression levels of several different types of ABPs have been successful in suppressing the phenotype of transformed cells (Gluck et al, 1993;Tanaka et al, 1995;Nikolopoulos et al, 2000), therefore implying that deregulation of ABPs directly contribute to oncogene-induced transformed phenotype of tumour cells. In the emerging story on the role of ABPs in cancer, profilin-1 (Pfn1 -a ubiquitously expressed G-actin-binding protein) is found to be expressed at a significantly low level in both human breast cancer tissue and a variety of breast carcinoma cell lines (Janke et al, 2000), pancreatic (Gronborg et al, 2006) and hepatic (Wu et al, 2006) carcinoma cells compared to their normal counterparts. These interesting observations appear to suggest that loss of Pfn1 expression may have a general relevance in cancer progression.…”
mentioning
confidence: 99%